Rheumatoid arthritis classification criteria: debatable problems - Yu. V. Muravyev; A. S. Misiyuk (Научно-практическая ревматология, 2019)
The paper discusses the issues of imperfect 1987 American College of Rheumatology (ACR) and the 2010 ACR/European League Against Rheumatology (EULAR) rheumatoid arthritis classification criteria and justifies the need for their correction.